Microbial colonization of basaltic glasses in hydrothermal organic-rich sediments at Guaymas Basin - Callac, Nolwenn; Rommevaux-Jestin, Céline; Rouxel, Olivier; Lesongeur, Françoise; Liorzou, Céline; Bollinger, Claire; Ferrant, Anthony; Godfroy, Anne (Frontiers in Microbiology, 2013)
Oceanic basalts host diverse microbial communities with various metabolisms involved in C, N, S and Fe biogeochemical cycles which may contribute to mineral and glass alteration processes at, and below the seafloor. In order to study the microbial colonization on basaltic glasses and their potential biotic/abiotic weathering products, two colonization modules called AISICS (“Autonomous In Situ Instrumented Colonization System”) were deployed in hydrothermal deep-sea sediments at the Guaymas Basin for 8 days and 22 days. Each AISICS module contained 18 colonizers (including sterile controls) filled with basaltic glasses of contrasting composition. Chemical analyses of ambient fluids sampled through the colonizers showed a greater contribution of hydrothermal fluids (maximum temperature 57.6°C) for the module deployed during the longer time period. For each colonizer, the phylogenetic diversity and metabolic function of bacterial and archaeal communities were explored using a molecular approach by cloning and sequencing. Results showed large microbial diversity in all colonizers. The bacterial distribution is primarily linked to the deployment duration, as well as the depth for the short deployment time module. Some 16s rRNA sequences form a new cluster of Epsilonproteobacteria. Within the Archaea the retrieved diversity could not be linked to either duration, depth or substrata. However, mcrA gene sequences belonging to the ANME-1 mcrA-guaymas cluster were found sometimes associated with their putative sulfate-reducers syntrophs depending on the colonizers. Although no specific glass alteration texture was identified, nano-crystals of barite and pyrite were observed in close association with organic matter, suggesting a possible biological mediation. This study gives new insights into the colonization steps of volcanic rock substrates and the capability of microbial communities to exploit new environmental conditions.